Videogame skins as an alternative investment instrument : the case of Counter Strike: Global Offensive. - Půta, Pavel; Rejthar, Jan; Kavřík, Dominik; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
This thesis deals with the game Counter Strike: Global Offensive in which there are collectable in-game items. The research consists of testing whether there is a relationship in the development of price of CS:GO items, specifically the loot box Operation Breakout Case and the Redline Field-Tested skin on AK-47 weapon, and the development of price of more traditional investment instruments. The examined period is 2020, in which the investment instruments were more volatile. Using the least square method, two regression analysis models are created from the data to further examine the price dependencies of the selected investment instruments. In the first model, in case of the Operation Breakout Case, there is no indication of any relationship in the price development with other investment instruments. In the second model, in the examination of the AK-47 Redline a dependency in price development with Bitcoin is found. However, this does not refute the results of the first model in any way, but rather confirms the necessity of researching the potential of individual items and not as a whole. Thus, the thesis shows the potential of CS:GO items entering an investors riskier portfolio as an alternative investment instrument, as these collectables might have a unique development in price, but on the other hand, they are still not researched in detail.
Vedoucí práce: Jan Rejthar
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor bakal. práce]; bakalářské práce; bachelor's theses